Impacts of solar activity on performance of the IRI-2012 model predictions from low to mid latitudes - Kumar, Sanjay (2015)
This study investigates the impacts of solar activity on the performance of the latest release of International Reference Ionosphere (IRI) model version 2012 (IRI-2012) predictions during the ascending phase of solar activity from 2009 to 2013. The study is based on the data of total electron content (TEC) retrieved from the Global Positioning System (GPS) at Singapore (NTUS) (geographic latitude 01.34°N, longitude 103.67°E, geomagnetic latitude 8.4°S), Thailand (CUSV) (geographic latitude 13.73°N, longitude 100.54°E, geomagnetic latitude 3.96°N), China (KUNM) (geographic latitude 25.02°N, longitude 102.79°E, geomagnetic latitude 15.15°N), Mongolia (ULAB) (geographic latitude 47.67°N, longitude 107.05°E, geomagnetic latitude 37.73°S), and Russia (IRKM) (geographic latitude 52.21°N, 104.31°E, geomagnetic latitude 42.28°S). The GPS-TEC has been compared with the IRI-2012 model TEC for three different options, namely, IRI-NeQ, IRI01-corr, and IRI-2001, for topside Ne over all the above five stations lying at different latitudes from equatorial-equatorial ionization anomaly (EIA) to mid-latitude regions but at around the same longitude line (104° ± 3°E). The study showed that the IRI model predictions for different topside options are different and significant in low-latitude region but insignificant in mid-latitude regions (except during winter season of high solar activity year 2012). During the period from 2009 to 2013, upon moving from low to high solar activity, the prediction nature (overestimation/underestimation) of IRI-2012 model changes significantly at EIA station KUNM of low-latitude region. The discrepancy in IRI-2012 model TEC as compared to GPS-TEC in low-latitude region is found to be larger and significant than in mid-latitude region (Mongolia and Russia). The discrepancy in the IRI-2012 model TEC with IRI-2001 topside is found to be maximum at equatorial station CUSV (RMSD 99%) during the solar minimum year 2009 and decreases moving towards high solar activity year. This suggests that significant improvements to the IRI-2012 model (hmF2 model) are required particularly in the equatorial regions taking the impacts of solar minimum year into account.